Pacifier-sucking habit duration and frequency on occlusal and myofunctional alterations in preschool children - Valdeane Simone Cenci NIHI; Sandra Mara MACIEL; Marta Essuane JARRUS; Fábio Mitugui NIHI; Carlos Luiz Fernando de SALLES; Renata Corrêa PASCOTTO; Mitsue FUJIMAKI (Sociedade Brasileira de Pesquisa Odontológica, 2015)
The objective of this study was to evaluate the association of pacifier-sucking habit with occlusal and oral myofunctional alterations in preschool children. Eighty-four 2- to 5-year-old children participated in the study. Data on duration and frequency of pacifier use were collected from parents or guardians. Occlusal and oral myofunctional characteristics were examined by a dentist and a speech therapist, respectively. Chi-square tests and Poisson regression were used to analyze the data. The occlusal characteristics that were significantly associated with a pacifier-sucking habit were anterior open bite, altered canine relation, posterior crossbite, increased overjet, and malocclusion. The oral myofunctional characteristics that were significantly associated with a pacifier-sucking habit were resting lip position, resting tongue position, shape of the hard palate, and swallowing pattern. The strongest associations were for anterior open bite (prevalence ratio [PR] = 11.33), malocclusion (PR = 2.33), altered shape of the hard palate (PR = 1.29), and altered swallowing pattern (PR = 1.27). Both duration and frequency of pacifier-sucking habit were associated with occlusal and oral myofunctional alterations. These results emphasize the need for pediatric dentists to advise parents and caregivers about the risks of prolonged pacifier use and refer children to professionals for multidisciplinary assistance to minimize these risks whenever necessary.